2020
DOI: 10.1155/2020/8260703
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Strategy Reveals the Effects of Hedysarum multijugum Maxim.-Radix Salviae Compound on Oxidative Capacity and Cardiomyocyte Apoptosis in Rats with Diabetic Cardiomyopathy

Abstract: Objective. To explore the effects of the Hedysarum multijugum Maxim.-Radix Salviae compound (Huangqi-Danshen Compound (HDC)) on oxidative capacity and cardiomyocyte apoptosis in rats with diabetic cardiomyopathy by a network pharmacology-based strategy. Methods. Traditional Chinese Medicine (TCM)@Taiwan, TCM Systems Pharmacology Database and Analysis Platform (TCMSP), TCM Integrated Database (TCMID), and High-Performance Liquid Chromatography (HPLC) technology were used to obtain and screen HDC’s active compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Systemic oxidative stress during late pregnancy and lactation is one of the main causes of impaired reproductive performance in sows [25]. GSH-Px and SOD are directly involved in the inactivation of reactive oxygen species as important barriers against oxidative damage in the body, where GSH-Px reduces hydrogen peroxide and SOD plays an important role in the elimination of oxygen radicals [26]. The results showed that CDF diet supplementation increased the activities of GSH-Px and SOD in the serum of sows.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic oxidative stress during late pregnancy and lactation is one of the main causes of impaired reproductive performance in sows [25]. GSH-Px and SOD are directly involved in the inactivation of reactive oxygen species as important barriers against oxidative damage in the body, where GSH-Px reduces hydrogen peroxide and SOD plays an important role in the elimination of oxygen radicals [26]. The results showed that CDF diet supplementation increased the activities of GSH-Px and SOD in the serum of sows.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al indicated that HMM treated ischemic stroke and protected patients from cerebral ischemia-reperfusion injury by regulating inflammation, oxidative stress, endoplasmic reticulum stress, and angiogenesis through signaling pathways, such as the PI3K-AKT, FoxO, TNF, HIF-1, Rap1, and VEGF signaling pathways ( 34 , 35 ). Zhang et al showed that HMM improved the general condition of diabetic cardiomyopathy in a rat model ( 36 ). Even for coronavirus disease of 2019 (COVID-19), HMM made its contribution to treating COVID-19 pneumonia by targeting PTGS2, TNF, and IL-6 and regulating the TNF and IL-17 signaling pathways ( 37 ).…”
Section: Discussionmentioning
confidence: 99%